Development of Word Square-Based Practice Module on The Topic of Writing Descriptive Text - Silvania Gusti Herdiana; Lidiyatul Izzah (Department of English Language Education, Universitas Muhammadiyah Purworejo, Indonesia, 2022)
The purpose of this study was to develop learning media in the form of a Word Square-based exercise module on the topic of writing descriptive text. This research is a research and development method using a development model, namely ADDIE (Analysis, Design, Development, Implementation and Evaluation). The subjects in this study were students of class X MIPA 1 SMAN 9 Tangerang. The data analysis used in this research is descriptive quantitative with percentage results. The results of the study obtained an assessment, among others; 1) material expert validation with 4 assessment aspects obtained an average percentage score of 83.09% with high and very valid criteria, 2) media expert validation with 3 assessment aspects obtained an average percentage score of 89.38% with very valid criteria, 3) validation of linguists with 3 aspects of assessment obtained an average percentage score of 84.16% with very valid criteria. The assessment of student responses on the small class test got an average score of 84.99% with high criteria and on the large class test an average percentage score of 84.33% with high criteria. Based on the results of the assessment, it can be stated that the learning media in the form of a Word Square-based exercise module that was developed is valid or suitable for use in learning to write descriptive text.